ChemInform Abstract: Isolation and Total Synthesis of Kirkamide, an Aminocyclitol from an Obligate Leaf Nodule Symbiont. Issue 44 (15th October 2015) - Sieber, Simon; Carlier, Aurelien; Neuburger, Markus; Grabenweger, Giselher; Eberl, Leo; Gademann, Karl
Abstract The new aminocyclitol, kirkamide (I), is isolated from leaf nodules of Psychotira kirkii.